2021
DOI: 10.3389/fmed.2020.615306
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Informatics Analysis of Transcriptome and Identification of Interacted Genes in the Glomeruli and Tubules in CKD

Abstract: Chronic kidney disease (CKD) is a complex disease in which the renal function is compromised chronically. Many studies have indicated the crosstalk between the tubule and the glomerulus in CKD progression. However, our understanding of the interaction of tubular and glomerular injury remains incomplete. In this study, we applied a meta-analysis approach on the transcriptome of the tubules and glomeruli of CKD patients to identify differentially expressed genes (DEGs) signature. Functional analysis of pathways … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…[ 48 ] Renal tubular injury may even occur earlier than glomerular dysfunction, [ 49 ] and cell injury molecules produced by damaged renal tubules may result in damage to glomeruli. [ 50 , 51 ] Tan et al. reported that mitigating renal tubular injury via reducing MMP‐7 expression provided significant protection against glomerular injury and proteinuria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 48 ] Renal tubular injury may even occur earlier than glomerular dysfunction, [ 49 ] and cell injury molecules produced by damaged renal tubules may result in damage to glomeruli. [ 50 , 51 ] Tan et al. reported that mitigating renal tubular injury via reducing MMP‐7 expression provided significant protection against glomerular injury and proteinuria.…”
Section: Discussionmentioning
confidence: 99%
“…[48] Renal tubular injury may even occur earlier than glomerular dysfunction, [49] and cell injury molecules produced by damaged renal tubules may result in damage to glomeruli. [50,51] Tan et al reported that mitigating renal tubular injury via reducing MMP-7 expression provided significant protection against glomerular injury and proteinuria. [52] Through il-lustrating the effect of T cell exosomal miR-186-5p on activating renal tubular TLR7/8 signal axis and initiating renal inflammation and tissue damage, our results support the notion that renal tubular injury induced by T cell miR-186-5p can initiate or aggravate glomerular damage, and provide the miR-186-5p-TLR7/8 signal axis as a novel mechanism underlying T cell-mediated renal dysfunction.…”
Section: Cells and Mir-186-5p Level In Either Cd8 T Cells Or Cd8 T-evsmentioning
confidence: 99%
“…A 2018 review summarised literature investigating transcriptomic analysis in the context of kidney disease (23), with a number of additional investigations published in recent years (146,(148)(149)(150)(151)(152)(153)(154)(155)(156)(157)(158)(159). An interesting study by Fan et al carried out RNA-seq analysis of kidney biopsies from early DKD, advanced DKD, or control patients, to reveal gene expression changes from healthy to disease states (158).…”
Section: Emerging Insights From Transcriptomic Analysis Of Ckdmentioning
confidence: 99%